Domestic versus export-led agricultural transformation: Evidence from Uganda’s dairy value chain - Van Campenhout, Bjorn; Minten, Bart; Swinnen, Johan (International Food Policy Research Institute, 2019)
Driven by increased demand from both local and export markets and facilitated by far-reaching liberalization and privatization policies, the dairy sub-sector in Uganda has undergone significant changes in the last decade. With a comparative advantage in milk production, the southwest of Uganda has started to attract considerable Foreign Direct Investment (FDI) in processing capacity, mainly targeting the export market. As a result, processing capacity increased five-fold and dairy became Uganda’s third most important export product, coming from negligible amounts a decade earlier. In this study, we use observational data collected at different nodes within the value chain to compare the structure of the chain and the roles and economic activities of different actors between export-led value chains and value chains that cater for the local market. Doing so allows us to identify the technological and institutional innovations that both result from the emergence of export-led dairy value chains and at the same time drive further upgrading. Our analysis underscores the importance of milk collection centers, which often take the form of farmer cooperatives, in providing many of the support services that enable other actors in the value chain to produce sufficient milk, and maintain milk sanitation levels necessary for an export sector to emerge.